Pertanggung Jawaban Tindak Pidana Lalu Lintas Pada Pn Tanjung Karang - Amanda Muntari; Incik Daffa Apriano; Yunika Sari Simatupang (Jurnal Multidisiplin Dehasen (MUDE), 2023)
One of the violations that often occur in Indonesia is traffic violations. The traffic crime itself is one of the acts of violation of the laws governing traffic. Violations committted by irresponsible persons can result in traffic accidents. Traffic violations are often herd with the term ticket in Indonesia, namely violations whose scope includes criminal law, consideringthat these actions are prohibited by applicable regulations resulting in the application of criminal sanctions as a form of accountability from the authorities